(untitled) (Revista de Artes Marciales Asiáticas, 2018)
The aim of this paper was to analyze the trends in judo research as a combat sport through a bibliometric analysis of scientific production indexed in the Web of Science database, starting with a group of 336 articles published between 2007 and 2017. By applying the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA-P) methodology, the study sample was reduced to 88 articles. Different types of variables were analyzed: a) institutional characteristics; b) sample-related characteristics; and c) research methods and tools. The results showed that the most productive years were 2014 and 2016, when the average number of authors was 4.56±1.79 and the average number of citations in the Web of Science was 9.25±11.9. The highest percentage of publications showed male samples, of high-performance level and under the discipline of training theory. The most commonly methodology used was the observational study with univariate statistics through instruments and observation tools. The most studied parameters were physiological and technical-tactical elements. It seems that judo as a combat sport attracts more scientific interest in its sporting and competitive side. Some suggestions are proposed to achieve a more specific analysis of the sport of judo, without contextualizing it as a combat sport.